Evaluation of green walls as a passive acoustic insulation system for buildings. (March 2015) - Azkorra, Z.; Pérez, G.; Coma, J.; Cabeza, L.F.; Bures, S.; Álvaro, J.E.; Erkoreka, A.; Urrestarazu, M.
Highlights: Weighted sound reduction index of 15 db were obtained by green wall. Weighted sound absorption coefficient of 0.40 were found by green wall. Green wall have significant potential sound insulation for vegetal architecture. Abstract: Greenery on buildings is being consolidated as an interesting way to improve the quality of life in urban environments. Among the benefits that are associated with greenery systems for buildings, such as energy savings, biodiversity support, and storm-water control, there is also noise attenuation. Despite the fact that green walls are one of the most promising building greenery systems, few studies of their sound insulation potential have been conducted. In addition, there are different types of green walls; therefore, available data for this purpose are not only sparse but also scattered. To gather knowledge about the contribution of vertical greenery systems to noise reduction, especially a modular-based green wall, two different standardised laboratory tests were conducted. The main results were a weighted sound reduction index ( Rw ) of 15 dB and a weighted sound absorption coefficient ( α ) of 0.40. It could be concluded that green walls have significant potential as a sound insulation tool for buildings but that some design adjustments should be performed, such as improving the efficiency of sealing the joints between the modular pieces.